Public administrators and policy agendas: some preliminaries to statute law making - Reynolds, Harry W. Jr. (2001)
Federal agencies are important players in the formulation of statutes. As an object of study and as part of the governmental process, academic public administration has shown little interest in the nature and extent of civil servants' involvement in this phenomenon, or in its ramifications. Making use of some data from survey research questionnaires as well as recently published histories of congressional enactments, this article seeks to open the door a little bit on this subject. Preliminary findings suggest that administrators are a significant influence from the earliest stages of statutes' evolution, impacting both important and run-of-the-mine enactments. That influence is evident in the frequency with which many agencies initiate and pursue their own legislative agendas year by year, draft their own bills, and participate in shaping policy objectives arising within Congress and among interest groups. By law, agencies are supposed to clear proposals through OMB before going to Congress, but as we will not, clearance can be a relative thing. Few proposed initiatives emanate directly from the White House. Tax and spending bills were excluded from the study, as were private bills. - Reproduced
Keywords: Civil service